2021
DOI: 10.1175/jtech-d-20-0085.1
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Ocean Color Component of the Aerosol Robotic Network (AERONET-OC)

Abstract: The Ocean Color component of the Aerosol Robotic Network (AERONET-OC) supports ocean color related activities such as validation of satellite data products, assessment of atmospheric correction schemes and evaluation of bio-optical models, through globally distributed standardized measurements of water-leaving radiance and aerosol optical depth. In view of duly assisting the AERONET-OC data user community, this work: i. summarizes the latest investigations on a number of scientific issues related to above-wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 54 publications
2
57
0
Order By: Relevance
“…It should be noted that these global match-ups were based on disparate instrumentation and quality standards [12,83] featuring lower accuracy in comparison to the AERONET-OC data used as a reference in this study [84]. The satisfactory performance in the 490-670 nm spectral range and the lower accuracy reported for the blue spectral bands confirm the findings with other radiometric validation exercises carried out in the Baltic Sea [24,[32][33][34]42,64,65]. Specifically, the observed bias values for R rs (555) and R rs (670) (8.33 × 10 −5 and 1.36 × 10 −4 sr −1 , respectively) were an order of magnitude lower than the thresholds defined in [78] (i.e., 4.25 × 10 −3 and 1.22 × 10 −3 sr −1 for the 555 and 670 nm bands, respectively).…”
Section: R Rs Validationsupporting
confidence: 79%
See 4 more Smart Citations
“…It should be noted that these global match-ups were based on disparate instrumentation and quality standards [12,83] featuring lower accuracy in comparison to the AERONET-OC data used as a reference in this study [84]. The satisfactory performance in the 490-670 nm spectral range and the lower accuracy reported for the blue spectral bands confirm the findings with other radiometric validation exercises carried out in the Baltic Sea [24,[32][33][34]42,64,65]. Specifically, the observed bias values for R rs (555) and R rs (670) (8.33 × 10 −5 and 1.36 × 10 −4 sr −1 , respectively) were an order of magnitude lower than the thresholds defined in [78] (i.e., 4.25 × 10 −3 and 1.22 × 10 −3 sr −1 for the 555 and 670 nm bands, respectively).…”
Section: R Rs Validationsupporting
confidence: 79%
“…This study presented recent improvements for the 1997-2019 Chl-a time series determined for the Baltic Sea from space-borne multi-sensor data. The accuracy of OC-CCI R rs for the Baltic Sea was assessed with AERONET-OC data acquired from 2005 to 2019 at three sites located in different sub-basins [64][65][66]. In agreement with other studies [64,65], results from the analysis of R rs match-up data showed that the external bands (412 and 670 nm) are affected by larger uncertainties: R rs (412) was characterized by a high dispersion, while R rs (670) had the largest bias.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations